2018
DOI: 10.3390/molecules23123153
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Electrical Properties and Field Dependency of BST and Nano-ZnO-Doped Silicone Rubber Composites

Abstract: Recently, composite materials with nonlinear dielectric or resistive properties performed well in electric field homogenization and space charge suppression in a high voltage transmission and distribution system. For the purpose of obtaining insulation materials with desirable dielectric and electrical resistance properties, we investigated several fillers with nonlinear electrical properties doped in silicon rubber composites, and their dependency on the temperature and field. The samples of silicone rubber c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Studies of PCC mixes incorporating various types of insulating fillers, such as recycled rubber and cycloaliphatic epoxy resin, indicated a reduction of tanδ in the range from 10-2 to 10-1 [38], which is in accordance with the results in this study. The tanδ factor of the PCC in this study showed similar values compared to other types of insulating coating materials, such as silicon rubber (0.05-0.20) [39]. Conversly, the dielectric loss factor of the PCC showed much higher values than other types of widely used insulating materials such as cross-linked polyethylene (from 10-3 to 10-4) and SF6 gas (less than 10-7) under a frequency of 50 Hz [40][41][42].…”
Section: Dielectric Losssupporting
confidence: 72%
“…Studies of PCC mixes incorporating various types of insulating fillers, such as recycled rubber and cycloaliphatic epoxy resin, indicated a reduction of tanδ in the range from 10-2 to 10-1 [38], which is in accordance with the results in this study. The tanδ factor of the PCC in this study showed similar values compared to other types of insulating coating materials, such as silicon rubber (0.05-0.20) [39]. Conversly, the dielectric loss factor of the PCC showed much higher values than other types of widely used insulating materials such as cross-linked polyethylene (from 10-3 to 10-4) and SF6 gas (less than 10-7) under a frequency of 50 Hz [40][41][42].…”
Section: Dielectric Losssupporting
confidence: 72%
“…At present, the research on material performance improvement is a hot issue [ 4 , 5 , 6 , 7 ], Movahedi found that the mechanical and tribological behavior of Ni(Al) was reinforced by Al 2 O 3 –13% TiO 2 nanoparticles [ 8 ]. A large number of studies have proved that dispersing nanoparticles into insulating oil can effectively improve the breakdown voltages and thermal conductivity of the insulating oil.…”
Section: Introductionmentioning
confidence: 99%
“…Under these conditions, it has been shown that the deformation rate for rubber is higher after the removal of the applied load, so that when PVC is added, the binary mixture will be subjected to a permanent deformation higher than the rubber. [ 27 , 28 ]. PVC-rubber-type mixtures that aimed to improve the use characteristics of PVC products have been presented in other scientific papers.…”
Section: Introductionmentioning
confidence: 99%